INTEGRASI MAGGOT BSF DAN LELE BERBASIS LIMBAH LADANG UNTUK USAHA TANI - Maria Ulfah; Azrita; Dessi Mufti; Yusra (LPPI UMN AL WASHLIYAH, 2026)
This Community Partnership Empowerment Program (PKM) was launched with the Landia Saiyo Sahati Farmer Group in Kanagarian Koto Tinggi to resolve the issue of post-harvest organic waste, which typically causes environmental pollution and hinders land reutilization. The program established an integrated business system centered on Black Soldier Fly (BSF) larvae (maggot) and catfish. This model utilizes agricultural waste as maggot feed, subsequently employing the high-protein maggot harvest as catfish feed, aiming to substantially reduce production costs and foster new productive economic opportunities. Implementation involved site surveys, socialization, technical training on maggot and catfish cultivation, technology transfer, and continuous mentoring, monitoring, and evaluation. The results confirmed the farmer group’s ability to execute a complete maggot production cycle; the majority of the maggot was utilized for catfish feed, with 15% reserved for breeding stock. Cultivated catfish are now being marketed through local traditional channels. Partner feedback was highly positive, with 91.2% of participants reporting significant enhancement of their knowledge and skills. Ultimately, the PKM contributes to the green economy by effectively managing organic waste and generating sustainable income through this integrated system.